Early-Warning Signals and Risk-Shifting Incentives - Laux, Volker; Zheng, Ronghuo (The Accounting Review, 2023)
ABSTRACT We study the optimal information system in a debt contracting setting in which managers can engage in value destroying risk-shifting behavior. The information system issues early-warning signals that allow lenders to take corrective actions such as liquidating unprofitable projects. When managers are empire builders, the optimal system exhibits a conservative bias that leads to excessive early-warning signals and excessive project liquidations relative to first best. In contrast, when managers have a strong preference for a quiet life, the optimal system exhibits a liberal bias that leads to insufficient early-warning signals and excessive project continuations. The broad intuition is that excessive liquidations (continuations) impose costs on managers who have a preference for empire building (a quiet life), and these costs are more severe when managers take excessive risks. The bias in the information system therefore permits managers to commit not to engage in risk shifting and facilitates debt financing. JEL Classifications: G30; G32; M40; M41.